Optimizing Competence of Village Apparatus in Improving the Quality Village Financial Reports - Farman, Fanji; Nusuki, Ina; Ahmad Andy Adinegara (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study was initiated due to apprehensions about the proficiency of village administrators and the integrity of village financial reports. Preliminary assessments revealed that numerous village authorities possessed inadequate experience in financial management and exhibited a limited comprehension of the Village Financial System (SISKEUDES), resulting in delays in the submission of financial reports. This study sought to accomplish three main objectives: (1) to evaluate the competence of village officials in Tanjungkerta Sub-district, Sumedang Regency; (2) to assess the quality of village financial reports in the region; and (3) to analyze the impact of village officials' competence on the quality of these financial reports. The research utilized a quantitative methodology, gathering data from 60 village official participants. The data underwent analysis by basic linear regression. The analysis indicated that: (1) the proficiency of village officials was rated as high; (2) the caliber of village financial reports was deemed very high; and (3) the proficiency of village officials exerted a positive and significant impact on the quality of village financial reports, with a coefficient of determination of 13.7%. The study concludes that augmenting the proficiency of village officials via training and education can enhance the quality and punctuality of financial reports, hence reinforcing successful local governance.